Youths and Deterrence: Columbia, South Carolina, 1979-1981 - Paternoster, Raymond ([Verlag nicht ermittelbar], 1986)
This is an investigation of a cohort of high school-aged youth in Columbia, South Carolina. Surveys were conducted in three consecutive years from 1979 to 1981 in nine high schools. Students were interviewed for the first time at the beginning of their sophomore year in high school. An identical questionnaire was given to the same students when they were in the 11th and 12th grades. The longitudinal data contain respondents' demographic and socioeconomic characteristics, educational aspirations, occupational aims, and peer group activities. Also included is information on offenses committed, the number of times respondents were caught by the police, their attitudes toward deviancy, and perceived certainty of punishment.